PRONUNCIATION DIFFICULTIES OF EFL LEARNERS IN INDONESIA: A LITERATURE STUDY - Fadillah, Alifa Camilia (Jurnal Budaya, 2020)
AbstractAs a lingua franca, English has become a prominent language to learn outside English-spoken countries. Especially in Indonesia, English slowly takes over the social life of Indonesian citizens and now serves several significant purposes, including within educational setting. Yet, within educational setting the burden to learn English become a challenging part for EFL learners in Indonesia, as they face several difficulties regarding the pronunciation of English words. Therefore, this paper serves as a pilot literature study to examine the research surrounding English pronunciation by EFL learners all over Indonesia. From 8 research papers compiled, it is found that there are three significant aspects that can be drawn out: 1) English vowels and consonants shift by EFL learners, 2) factors influencing Indonesian EFL learnersâ€™ pronunciation, and 3) the instruments and media used by Indonesian researchers to monitor the pronunciation. It shows that indeed there are vowels and consonants shift when EFL learners try to pronounce English words, and the factors that affect their pronunciation includes their mother tongue influence, the exposure of target language, and lastly their biological factor such as their ear perception. It is also revealed that there are not much of instruments used by Indonesian researchers to monitor the pronunciation of either research participants or native speakers of English within the scope of their research. There are only two papers that use Speechnote and Praat as their instruments, and other researchers rely on their own perception when monitoring the English sounds.Keywords: pronunciation difficulties, EFL learners, vowels and consonant shift, instruments, Speechnote, PraatÂ AbstrakSebagai lingua franca, bahasa Inggris telah menjadi bahasa yang paling menonjol untuk dipelajari oleh masyarakat yang tidak menggunakan bahasa Inggris sebagai bahasa utamanya. Contohnya, pengaruh bahasa Inggris di Indonesia sudah menjalar ke berbagai aspek kehidupan masyarakat dan memiliki berbagai peran khusus, termasuk perannya di ranah pendidikan. Meskipun begitu, para pelajar EFL (English as a foreign language) di Indonesia masih merasa kesulitan dalam mempelajari bahasa Inggris, utamanya ketika dihadapkan dengan pengucapan kata-kata berbahasa Inggris. Maka dari itu, studi literatur ini bertujuan untuk mengobservasi penelitian-penelitian yang meneliti pengucapan kata-kata bahasa Inggris oleh pelajar EFL di seluruh Indonesia. Dari 8 penelitian yang dikumpulkan, ada tiga aspek penting yang mendasari penelitian-penelitian tersebut, antara lain: 1) pergeseran suara vokal dan konsonan bahasa Inggris oleh pelajar EFL, 2) faktor-faktor yang mempengaruhi akuratnya pengucapan para pelajar EFL Indonesia, dan 3) instrumen atau media yang dipakai oleh para peneliti Indonesia untuk memonitor akurasi pengucapan. Dari observasi, ditemukan bahwa memang ada pergeseran suara vokal dan konsonan ketika para pelajar EFL dites pengucapannya. Pengaruh bahasa ibu, paparan bahasa target, dan faktor biologis seperti persepsi telinga menjadi faktor-faktor yang mempengaruhi akurasi pengucapan para pelajar yang diteliti. Terakhir, ditemukan juga bahwa tidak banyak instrumen dan media yang digunakan untuk memonitor akurasi pengucapan dalam penelitian-penelitian ini. Hanya ada dua penelitian yang menggunakan Speechnote dan Praat sebagai instrumennya, sedangkan peneliti lainnya menggunakan persepsi mereka sendiri ketika memonitor pelafalan kata-kata berbahasa Inggris.Kata kunci: kesulitan pengucapan, pelajar EFL, pergeseran vokal dan konsonan, instrument, Speechnote, Praat